2009
DOI: 10.1161/circulationaha.108.803916
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Improves Cardiac Function and Alters Myocardial Substrate Metabolism Without Affecting Cardiac Triglyceride Accumulation and High-Energy Phosphate Metabolism in Patients With Well-Controlled Type 2 Diabetes Mellitus

Abstract: Background-Cardiac disease is the leading cause of mortality in type 2 diabetes mellitus (T2DM). Pioglitazone has been associated with improved cardiac outcome but also with an elevated risk of heart failure. We determined the effects of pioglitazone on myocardial function in relation to cardiac high-energy phosphate, glucose, and fatty acid metabolism and triglyceride content in T2DM patients. Methods and Results-Seventy-eight T2DM men without structural heart disease or inducible ischemia as assessed by dobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
171
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(183 citation statements)
references
References 50 publications
(52 reference statements)
9
171
2
1
Order By: Relevance
“…This finding in men makes sense given that their palmitate clearance decreased, and they had slightly higher plasma FA levels. These myocardial FA findings are in contrast with another study, which demonstrated a decline in FA oxidation with metformin (23). The reasons for this dis- …”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…This finding in men makes sense given that their palmitate clearance decreased, and they had slightly higher plasma FA levels. These myocardial FA findings are in contrast with another study, which demonstrated a decline in FA oxidation with metformin (23). The reasons for this dis- …”
Section: Discussioncontrasting
confidence: 89%
“…Alternatively and/or in addition, some studies suggest sexrelated differences in the generation of oxidative stress and the response to oxidative stress (6,11), and oxidative stress is linked to cardiac dysfunction (1). The lack of correlation between functional and metabolic changes is at odds with studies in experimental models of T2DM (25) but consistent with reports in T2DM patients (23). The lack of correlation may reflect the fact that our patients were relatively healthy, well-controlled, and only exhibited mild diastolic dysfunction.…”
Section: Whole Body Substrate Kineticsmentioning
confidence: 61%
See 2 more Smart Citations
“…Moreover, it is also important to note that the use of hypoglycemic, lipidlowering and anti-hypertensive drugs was not significantly different between patients with and without NAFLD. Again, no patients were treated with pioglitazone or glucagon-like peptide-1 receptor agonists, which have been shown to reduce hepatic steatosis [1,9,25] and improve cardiac function [26,27]. Finally, our novel finding of a significant association between NAFLD and larger left atrial volume might also be of pathophysiological relevance in the explanation of recent observations documenting that type 2 diabetic patients with NAFLD are at risk of atrial fibrillation [28,29].…”
Section: Discussionmentioning
confidence: 73%